Cytotoxic Potential of Bacillus cereus Strains ATCC 11778 and 14579 Against Human Lung Epithelial Cells Under Microaerobic Growth Conditions - Kilcullen, Kathleen; Teunis, Allison; Popova, Taissia G.; Popov, Serguei G. (Frontiers in Microbiology, 2016)
Bacillus cereus, a food poisoning bacterium closely related to Bacillus anthracis, secretes a multitude of virulence factors including enterotoxins, hemolysins, and phospholipases. However, the majority of the in vitro experiments evaluating the cytotoxic potential of B. cereus were carried out in the conditions of aeration, and the impact of the oxygen limitation in conditions encountered by the microbe in natural environment such as gastrointestinal tract remains poorly understood. This research reports comparative analysis of ATCC strains 11778 (BC1) and 14579 (BC2) in aerated and microaerobic (static) cultures with regard to their toxicity for human lung epithelial cells. We showed that BC1 increased its toxicity upon oxygen limitation while BC2 was highly cytotoxic in both growth conditions. The combined effect of the pore-forming, cholesterol-dependent hemolysin, cereolysin O (CLO), and metabolic product(s) such as succinate produced in microaerobic conditions provided substantial contribution to the toxicity of BC1 but not BC2 which relied mainly on other toxins. This mechanism is shared between CB1 and B. anthracis. It involves the permeabilization of the cell membrane which facilitates transport of toxic bacterial metabolites into the cell. The toxicity of BC1was potentiated in the presence of bovine serum albumin which appeared to serve as reservoir for bacteria-derived nitric oxide participating in the downstream production of reactive oxidizing species with the properties of peroxynitrite. In agreement with this the BC1cultures demonstrated the increased oxidation of the indicator dye Amplex Red catalyzed by peroxidase as well as the increased toxicity in the presence of externally added ascorbic acid.